Interacción reproducción-nutrición en los animales domésticos : ¿es la leptina la clave? (1999)
ABSTRACT: Numerous factors including energy intake, vitamins, minerals, and fatty acids influence reproductive function in domestic animal by means of their effects both on the hypothalamus-pituitary axis and directly on the gonads. Metabolic condition has been amply demonstrated to affect reproductive capacity. Development of adipose tissue in conjunction with production and secretion of cytokines and other proteins by fat cells are expected to exercise control over metabolic processes. In this context, leptin a recently discovered hormone secreted by adipose tissue appears to play a preponderant role in regulating appetite, energy expenditure and gonadotropin secretion. Currently the sites of action and potential effects of leptin on reproduction are being elucidated.